Il teatro politico in Europa: Da Est a Ovest, 2007-2014 - Shevtsova, Maria (Mimesis Journal, 2024)
What political theatre may be in contemporary times and in what sense it is ‘political’ are the core issues of this article. Maria Shevtsova discusses examples from within a restricted period, 2007 to 2014, but from a wide area that begins in Eastern Europe – Russia, Ro-mania, Hungary, Poland – and moves to Germany and France. Her examples are principally productions by established ensemble theatre companies and her analysis is framed by a brief discussion concerning independent theatres, ‘counter-cultural’ positions, and institutional and institutionalized theatres. This latter group is in focus to indicate how political theatre in the seven years speci- fied has been far from alien to, or sidelined from, national theatres, state theatres, or other prestigious companies in receipt of state subsidy. Two main profiles of recent political theatre emerge from this research, one that acknowledges political history, while the other critiques neoliberal capitalism; there is some unpronounced overlap between the two. Productions of Shakespeare feature significantly in the delineated theatrescape.